New Findings in Prominent Lower Eyelid Fat Pads Possibly Contributing to Their Etiology: Two Prospective Studies - Iliana E. Sweis, MD; Bryan C. Cressey, JD (Plastic and Reconstructive Surgery, Global Open)
Background:. Little is known about the actual composition of prominent orbital fat pads. It was incidentally noted that hyaluronidase injections in prominent lower eyelid fat pads attenuated them, suggesting prevalence of hyaluronic acid (HA), and raising questions regarding their etiology. This led to 2 institutional review board studies: The first quantified HA concentration in orbital fat pads and assessed possible correlation between HA levels and degree of lower eyelid puffiness. The second determined if regular hyaluronidase injections in prominent lower eyelid fat pads impacted their size to uncover a possible role of intrinsic HA and its hydrophilic properties in their etiology. Methods:. Lower eyelid orbital fat harvested from 20 filler-naive blepharoplasty patients underwent enzyme linked immunosorbent assay for HA quantification. A separate group of 14 filler-naive patients requesting nonsurgical treatment of lower eyelid puffiness were treated with a series of hyaluronidase injections. Results:. HA levels in prominent eyelid orbital fat pads averaged 39.3 µg/mg of the dry weight, higher than reported in other solid human tissues. Orbital fat HA levels correlated with the degree of clinical puffiness. Hyaluronidase attenuated lower eyelid puffiness in 78.6% of patients. The extent and duration of improvement varied between responders but increased with repetitive injections. Conclusions:. Prominent orbital fat pads have a higher HA concentration than reported in other solid human tissues. HA hydrophilic properties likely contribute to fat pad edema manifesting as puffiness. Attenuation of prominent lower eyelid fat pads following hyaluronidase injections further implicates intrinsic HA in the etiology of prominent eyelid fat pads.